Morphing Wing I - finite element modelling of a NiTi SMA wire - Wan A Hamid, Wan Luqman Hakim; Iannucci, Lorenzo; Robinson, Paul (International Center for Numerical Methods in Engineering (CIMNE), 2017)
This research aims to model the shape memory effect (SME) of a shape memory alloy (SMA) wire in a commercial explicit finite element analysis (FEA) software, Ls-Dyna. A user defined material (UMAT) model was developed by implementing a one dimensional constitutive model into Ls-Dyna. A simple structure consisting of one SMA wire connected to a linear spring in series was analysed using Ls-Dyna. One complete heating-cooling cycle was applied on the SMA wire, and the resulting stress and strain were validated by analytical solutions. This SMA model was further tested for mesh sensitivity, for a range of values of key parameters, and for fully-constrained and constant load cases. Finally, actuation of several morphing aerofoil sections was studied. Among the proposed aerofoil configurations, an aerofoil with a corrugated plate in between the D-nose spar and the trailing edge (TE) section, with one SMA wire in each cell, provided the highest TE deflection. The results show the applicability of the current model in actuation of the morphing aerofoils.